Weather insurance: a tool for social protection under climate change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Ahead of World Food Day, Sonja Vermeulen, Head of Research for CCAFS, answered questions on boosting resilience and smallholder farmer income under climate change. The video was originally broadcast on Periscope on 12 October.